Implementasi Model Problem-Solving pada Mata Pelajaran Dasar Teknik Ketenagalistrikan di Sekolah Menengah Kejuruan - Elianingsih, Stevany; Myori, Dwiprima Elvanny (Jurusan Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2024)
The observation conducted in the Electrical Power Installation Engineering (TITL) department at SMKN 5 Solok Selatan reveals that the teaching methods currently used in the classroom are conventional, such as lecture-based approaches, which are perceived as straightforward and relatively easy. This has led to a lack of engagement among students in the Basic Electrical Engineering subject, resulting in passive learning. This study aims to analyze the implementation of the problem-solving model in the Basic Electrical Engineering course for class X TITL at SMKN 5 Solok Selatan. The research employed a quantitative approach with an experimental design. Results from student assessments through pretests and posttests demonstrated a significant increase in achievement, with a notable improvement in scores. The normalized gain score analysis indicated a medium average gain value. Additionally, the model was found to be fairly effective. Before implementing the problem-solving model, students' skill assessment scores were lower, but these scores increased afterward, showing a marked improvement. Based on these findings, it can be concluded that implementing the problem-solving learning model can enhance the learning outcomes of Basic Electrical Engineering for class X TITL students at SMK Negeri 5 Solok Selatan.